The importance of work conditions and health for voluntary job mobility: a two-year follow-up - Reineholm Cathrine; Gustavsson Maria; Liljegren Mats; Ekberg Kerstin (BMC, 2012)
Abstract Background Changing jobs is part of modern working life. Within occupational health, job mobility has mainly been studied in terms of employees' intentions to leave their jobs. In contrast to actual turnover, turnover intentions are not definite and only reflect the probability that an individual will change job. The aim of this study was to determine what work conditions predict voluntary job mobility and to examine if good health or burnout predicts voluntary job mobility. Methods The study was based on questionnaire data from 792 civil servants. The data were analysed using logistic regressions. Results Low variety and high autonomy were associated with increased voluntary job mobility. However, the associations between health and voluntary job mobility did not reach significance. Possible explanations for the null results may be that the population was homogeneous, and that the instruments for measuring global health are too coarse for a healthy, working population. Conclusions Voluntary job mobility may be predicted by high autonomy and low variety. The former may reflect that individuals with high autonomy have stronger career development motives; the latter may reflect the fact that low variety leads to job dissatisfaction. In contrast to our results on job content, global health measurements are not strong predictors of voluntary job mobility. This may be because good health affects job mobility through several offsetting channels, involving the resources and ability to seek a new job. Future work should use more detailed measurements of health or examine other work settings so that we may learn more about which of the offsetting effects of health dominate in different contexts.